Utilization of solar energy for power generation in Nigeria (2012)
This study presents the viabilities for power generation in Nigeria through the utilization of the sun’s energy. Solar-thermal and photovoltaic options were discussed. It highlights the basic science for the design and selection of com-ponents for successfully harnessing solar power. Requirements for solar panel placement and orientation were also high-lighted. It emphasizes that the knowledge and experience gained in solar energy as an abundant and convenient energy source, can play a role in steering the nation toward a permanent and sustainable development. The energy demand in Nigeria far outweighs the supply which is epileptic in nature. The acute electricity supply hinders the country’s develop-ment notwithstanding the availability of vast natural resources in the country. Our ability to continue the trend for afford-able energy will be severely tested in the coming decades, as evidenced by the widening trade imbalance, collapse of big manufacturing companies, sharp increase in the cost of doing business just to mention but a few. It is the issue of utilizing the sun’s silent, inexhaustible, and non-polluting resource for power generation in Nigeria that this work addresses; hence it is the long-range review of the energy problem.